A study of histological changes during development of human fetal kidney in later half of gestation - Thakur, Rajni; Tiwari, Anjana (International Journal of Research in Medical Sciences, 2017)
Background: Prenatal period is a very crucial time for human development. It is important to know the normal developmental of human kidney for better understanding of various congenital renal conditions. Methods: This study was conducted in the department of anatomy, Pt. J. N. M. medical college Raipur, Chhattisgarh, India. The materials for study (50 fetuses of gestational age between16 week to 40 weeks from cases of abortions, stillbirth from premature and normal deliveries with apparently normal history of gestation) were obtained from the labour room of the R. N. T. district hospital Kondagaon, Chhattisgarh, India. Fetal kidneys were dissected out; histological slides were made, stained with Hematoxylin and eosin and observed under light microscope. Results: A Subcapsular nephrogenic zone was seen in all kidneys up to 36 weeks of gestational age. Differentiation of kidney into cortex and medulla was seen in all the specimens. Presence of Bowman’s space was seen in 90-95% of glomeruli and vascular pole were present in 65-70% of glomeruli, in all specimens of different gestational age. Parietal epithelial lining of Bowman’s capsule was lined by cuboidal epithelium in immature glomeruli but this showed a gradual transition to a flat variety, with the further maturation of the glomeruli. Proportion of glomeruli with many lobulations, went on increasing with increasing gestational age. Conclusions: From the above findings, it can be concluded that although formation of new glomeruli occurs up to 36 weeks of intrauterine life, differentiation and maturation continues until the last week of third trimester of gestation.